Exploratory analysis of fight-ending punches in the ultimate fighting championship™ mixed martial arts promotion - Barley, O. R.; Doherty, C. S.; Scanlan, M.; Tapsell, L. C.; Wilson, C.; Giustiniano, J.; Plush, M. G.; Vial, S. (International Journal of Sports Science & Coaching, 2025)
Punching is a crucial element of mixed martial arts (MMA), often leading to knockouts (KO) or technical knockouts (TKOs). This study explored the relative foot positions of athletes, their stances, punch type executed, and the reliability of these variables to provide insights into effective punch application in MMA. We retrospectively examined MMA contests from the Ultimate Fighting Championship that ended via KO/TKO (2020 to 2022). Data were sourced from publicly available videos on the internet. Three analysts, each with at least three years of experience in striking combat sports and competitive MMA, conducted observations independently. Only critical strikes where all analysts agreed on the time and type of punch were included. Inter-rater reliability was assessed using the Cohen's kappa coefficient statistic (K). The k-means cluster analyses were used to identify the most frequently occurring front foot positions (FFP) and punch types (PT). All variables, except for the back foot position, demonstrated substantial or greater reliability (K = 0.64-0.92). Out of 271 contests, the most common fight-ending punches were the rear straight (n = 77, 29.2%), front hook (n = 71, 26.9%), and rear hook (n = 63, 23.9%). According to the cluster analysis, overall, the most common PT for athletes of the same stance was an outside FFP with a rear straight punch (n = 35, 14.4%). For competitors in opposite stances, the most common FFP was outside, with a rear hook punch (n = 16, 22.8%). Identifying common PTs, FFPs, and stances offers valuable insights for technical coaching and talent identification, aiding in refining training methods and improving MMA performance.